Augmentation of Oridonin-Induced Apoptosis Observed With Reduced Autophagy - Cui Qiao; Tashiro Shin-ichi; Onodera Satoshi; Ikejima Takashi (Elsevier, 2006)
Abstract.: Our previous studies showed that oridonin could induce apoptosis in HeLa cells; and in this study, we further investigated autophagy induced by oridonin in HeLa cells and the relationship between apoptosis and autophagy. HeLa cells were exposed with oridonin after 3-methyladenine (3-MA) pre-culture, and we evaluated the growth inhibitory ratio, morphologic changes, DNA fragmentation, proteins expression as well as autophagic and apoptotic levels. Oridonin inhibited the proliferation of HeLa cells in vitro and induced autophagy. Oligo-nucleosomal fragementation of DNA as well as increased activities of Bax proteins were induced by oridonin, but the expression of p-Bcl-2 protein was reduced. In the condition of oridonintreatment, when the inhibitor of phosphoinositide 3-kinase (PI3K), wortmannin, was applied, the autophagic level was significantly decreased, while the apoptotic level was increased, indicating that PI3K is a key regulator of both autophagy and apoptosis. Akt, down-stream factor of PI3K, was activated in autophagic process but suppressed in apoptosis in this study. In addition, when autophagy was blocked by 3-MA, the expression of SIRT-1 was decreased, indicating SIRT-1 contributed to autophagy. Taken together, oridonin simultaneously induced HeLa cell both apoptosis and autophagy in HeLa cells, and inhibition of autophagy contributes to upregulation of apoptosis. Keywords:: oridonin, apoptosis, autophagy